Reproductive Medicine for Clinical Practice Medical and Surgical Aspects (Reproductive Medicine for Clinicians,, 2018)
This first volume of the series of the International Academy of Human Reproduction focuses on new aspects of reproductive medicine, from the professional responsibility model of ethics to the areas of high clinical involvement in human reproduction, such as endometriosis, polycystic ovary, family planning and post-coital contraception. The book discusses fertility and assisted reproductive techniques in the context of genetics and epigenetics as well as psychosomatic and longevity aspects. In addition, it presents new technologies and therapeutic strategies to improve IVF results and prevent ovarian hyperstimulation syndrome, as well the new challenges and the future of imaging in reproduction. Menopause and the effects of estrogens on atero-prevention, mood, and more generally the reproductive hormones impact on dementia and healthy aging are also covered. Further, it includes a section devoted to innovative aspects of gynecological surgery, discussing the treatments of vaginal aplasia, reproductive microsurgery and technological breakthroughs in pelvic organ prolapse surgery. Last, but not least, it examines the syndromic aspects of preterm birth. This volume is a useful and comprehensive tool for gynecologists, obstetricians, endocrinologists and all specialists who deal with women's reproductive health.